Parliament: A Question of Management - Barrett, V M (ANU Press, 2022)
For centuries scholars and practitioners have studied parliament and its potential reform from an institutional perspective. Until now, few authors have addressed in depth the internal relationships among parliamentary actors, their competing beliefs and their influence on parliament's effectiveness. Parliament is overwhelmingly an agonistic institution, and competition for status, resources, influence and control has pervaded its administration and impeded reform. Parliaments appear to struggle with the concept of institutional management. The doctrine of exclusive cognisance or sole jurisdiction implies that parliament, and only parliament, should retain control of its internal business and processes. But why is parliament considered to be unique among other public institutions, and why do parliaments appear to resist or even defy attempts to manage them more effectively? At a time when the public is losing confidence in governments, politics and political institutions, parliament's role as a broker of ideas and a forum for deliberative policymaking is under threat. In an institution where no one has overall authority and direction, staying relevant and managing public expectations present major challenges for its members and administrators. This book examines parliamentary management in the national parliaments of Australia and the United Kingdom. Without claiming to be a 'how to' book, it attempts to provide a relatable account of how parliamentary officials and members of parliament carry out their inherently complex roles and how they might be assisted by contemporary public management approaches.